(untitled) (Journal of Bio-Science, 2026)
The spotted snakehead fish, scientifically known as Channa punctata, is highly popular in Bangladesh under both fresh and dry conditions. This work aimed to use both traditional and molecular methods to discover the fungus associated with dried C. punctata. The fungus’s cultural characteristics were also examined. Aspergillus flavus, a very common fungus in dry C. punctata, was characterized molecularly using a 594 bp PCR product of its ITS (internal transcribed spacer) region. The sequence was submitted to NCBI under accession number PX122472.1 (JUF0125). The molecular phylogenetic tree derived from it revealed that A. flavus species complex had 100% sequence similarity. Mycelial growth characteristics analysis of the fungus revealed that Hennerberg (56 mm) and yeast extract mannitol (28 mm) culture media, respectively, showed the highest and lowest mycelial growth rates. The optimal pH and temperature for mycelial growth of A. flavus were 7 and 30℃, respectively. To the best of our knowledge, this experimental identification of the dry fish fungus Aspergillus flavus associated with C. punctata is the first report and confirmation of a fungus in Bangladesh using both classical and molecular approaches. J. Bio-Sci. 33(2): 21-28, 2025